Comparing Mortgage Credit Risk Policies : An Options-Based Approach - Buckley, Robert (World Bank, Washington, DC, 2014)
Buckley, Karaguishiyeva,Van Order, and Vecvagare analyze the structure of approaches to mortgage credit risk that are now being used in a number of OECD and transition economies. The authors' basic approach is to show how option pricing models can help measure and evaluate the risks of various schemes. They find that mortgage default insurance can be a cost-effective tool for both improving housing affordability and efficiently addressing some of the rationing that characterizes this market. When correctly structured, as it is in a number of transition and market countries, this kind of program can be expected to reduce nonprice rationing at an actuarially fair price. At the same time, considerable care must be exercised in the development of such instruments. Geographical risk diversification, particularly across borders, can play a major role in the success of these programs. Such diversification could be important not only in smaller transition economies but in EU countries as well.